Pengaruh Optimalisasi Dinas Jaga Pelabuhan Terhadap Proses Bongkar Muat Kontainer - Antony, Fizenta Kevin; Hendartono, Ario; Ari Ani Dyah Setyoningrum (Majalah Ilmiah Gema Maritim, 2023)
Watchkeeping at ports is necessary to improve the safety of lives, cargo, and the surrounding environment. Watchkeeping and supervision are required in the process of loading and unloading containers. Supervision that could be more optimal can cause several problems in the loading and unloading process. These problems include loading errors, damage to ship inventory, and can endanger human safety. This research aims to measure the effect of optimising the port guard service on the loading and unloading process. This research is a type of qualitative descriptive research. Data collection techniques were conducted using interviews, observation, documentation, and literature study—data analysis techniques through data reduction, presentation, and concluding/verification. The results of this research state that implementing watchkeeping duties influences the loading and unloading process. The lack of understanding by ship crews regarding the STCW 1978 Amendment 2010 regulations regarding the implementation of watchkeeping and the lack of responsibility of watchkeeping personnel in carrying out outstanding orders are obstacles to loading and unloading containers.